Which institutional investors drive corporate sustainability? A systematic literature review - Patrick Velte (Business Strategy and the Environment, 2022)
In this article, we review recent archival research (66 studies) on the influence of institutional ownership (IO) heterogeneity on corporate sustainability. Relying on an agency-theoretical framework, we differentiate between various types of IO and their nature. We found that most prior research concentrates on the impact of IO heterogeneity on corporate sustainability performance. Long-term, sustainable, and foreign IO leads to better ESG/CSR outputs. Based on the business case argument for corporate sustainability, long-term institutional investors moderate the positive link between corporate sustainability and future financial performance. We provide useful recommendations for future research by focusing on endogeneity concerns as methodological challenges and content-related proposals for future research designs.
Keywords: 650; agency theory; corporate governance; corporate social responsibility; institutional investors; institutional ownership; monitoring